Bridging the gap between organisational practices and cyber security compliance: Can cooperation promote compliance in organisations? - Daud, Maslina; Rasiah, Rajah; George, Mary; Asirvatham, David; Thangiah, Govindamal (Universiti Malaysia Sarawak, 2018)
Drawing on public goods and institutional theory, this study examines the mediation effect of cooperation on the relationship between organisational practices, namely, top management commitment (TMC), structured security processes (SSP) and security investment (SI) and cyber security compliance in organisations. Using data from Malaysia’s critical sectors, ordinal regression was used to establish the odds of security compliance with security practices adjusted for job portfolio, security responsibility and educational levels. The results show that cooperation mediates TMC and SSP in achieving security compliance. The indirect effect of cooperation on these practices shows its subtle influence, which was not demonstrated in previous studies. These results also support the non-excludable characteristic of cyber security as a public good where cooperation overrides free-riding when security aspects are involved.